ANALISIS POTENSI DAN EFEKTIVITAS PENERIMAAN PAJAK REKLAME DI KOTA MANADO - Sarundayang, Markus Stenny; Karamoy, Herman; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Advertisement tax is a tax on the conduct of advertisements. Advertising is an object, tools, or media of varying shapes and styles used for the introduction, advocating and praising goods, services or persons or to draw public attention, placed or seen, read and or heard from a place by the public. This research aimed to know find out the magnitude of potential tax advertisement in Manado city and to know the effectiveness of advertisement tax revenue as a source of PAD Manado City. Research uses quantitative descriptive method that is analyzing the target data and the realization of acceptance of advertisement tax year 2012-2016 using the ratio of effectiveness and analysis of historical data. From the results of research indicate that the effectiveness level of advertisement tax of year 2010-2014 got category "less effective", and year 2015-2016 â€œvery effectiveâ€ Based on the calculation of historical data, the potential acceptance of Advertisement Tax of Manado City in 2017 is Rp. 11.010.071.843,-.Keywords: Advertisement Tax, Local Revenue, Potential, Effectiveness